“God gave you a special child because you are special”: difficulties, coping strategies, and parental burnout of Jewish mothers – a qualitative study - Yifat Findling; Sivia Barnoy; Michal Itzhaki (Frontiers in Psychology, 2023)
Background“Parental Burnout” is a specific syndrome resulting from an imbalance between continuous exposure to chronic parenting stress and available protective resources. Mothers of children with special needs have an increased risk of Parental Burnout due to dealing with various difficulties from carrying out long-term childcare.PurposeTo examine difficulties, coping strategies, and PB (risk factors and protective resources), among ultra-Orthodox and non-Orthodox Jewish mothers of children with special needs with high or low levels of Parental Burnout.MethodsA qualitative study. Twelve mothers of children with special needs identified with high or low Parental Burnout via a quantitative study were interviewed. The constant-comparative analysis method was used to analyze the findings.FindingsThree themes and twelve categories emerged: 1. Difficulties involved in motherhood with six categories: (a) caregiver burden, (b) task overload, (c) physical and mental self-neglect, (d) environmental, couple-hood, family and social neglect, (e) recognizing the gap between their child with special needs and other children of the same age, (f) the environment’s contradictory expectations from the mother; 2. Coping strategies with four categories: (a) practical, (b) spiritual, (c) social and (d) emotional; and 3. Parental Burnout, consequences and coping with two categories: (a) personal and environmental risk factors (e.g., fear of the future, difficulty in trusting others in taking care of their child), and (b) personal and environmental protective resources (e.g., sharing similar circumstances with other mothers, a belief in God).Conclusions and implicationsThe findings contribute to understanding the unique difficulties, coping strategies and differences in risk factors and protective resources of Parental Burnout among ultra-Orthodox and non-Orthodox Jewish mothers of children with special needs. In order to alleviate the difficulties experienced by mothers and thus also reduce Parental Burnout risk factors and provide effective protective resources, it is recommended to develop empirically based professional guidance for policymakers, child development specialists, nurses, physiotherapists, and informal caregivers.